Thermoelectric material and preparation method thereof
The preparation of double half-Heusler alloy thermoelectric materials through heterovalent element substitution and high-energy ball milling methods has solved the problem of high lattice thermal conductivity of traditional materials, achieved low lattice thermal conductivity and high-efficiency thermoelectric conversion efficiency, and expanded its content in Application potential in the field of high temperature thermoelectricity.
Patent Information
- Application Number
- CN202411597717.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The higher lattice thermal conductivity of traditional half-Heusler compounds limits their thermoelectric performance and is difficult to show higher efficiency in the field of medium and high temperature thermoelectric.
The thermoelectric material with low lattice thermal conductivity of double half-Heusler alloys was prepared by substitution of heterovalent elements. High-energy ball milling method and discharge plasma sintering technology were used, combined with high-temperature annealing treatment, the Sc/V ratio and Ni doping concentration were adjusted to reduce crystallization Grid thermal conductivity.
The low lattice thermal conductivity of the dual half-Heusler alloy thermoelectric material is achieved, which improves the thermoelectric conversion efficiency of the material, and makes it have broader application prospects in the field of medium and high temperature thermoelectric.
Smart Images

Figure CN119433322A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoelectric materials, relates to a thermoelectric material and a preparation method thereof, and particularly relates to a double half-Heusler alloy thermoelectric material with low lattice thermal conductivity and a preparation method thereof. Background Art
[0002] Thermoelectric materials are crucial in the reversible conversion of energy. They can convert heat into electricity or generate heat from electricity. Therefore, they are of great significance in the development and utilization of sustainable energy. Thermoelectric generators use these materials to recycle waste heat, providing the possibility for the improvement of green energy technology. The significant advantage of thermoelectric generators is that they have no moving parts and zero emissions, making them environmentally friendly and low-maintenance energy conversion devices. The energy conversion efficiency of thermoelectric devices is directly related to the dimensionless figure of merit (zT), which is calculated as zT = S2σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. Although thermoelectric devices have the potential to alleviate the energy crisis and reduce environmental pollution, there are still great challenges in improving the energy conversion efficiency due to the complex dependence of their internal electronic and thermal conductivity parameters.
[0003] In recent years, researchers have proposed a variety of strategies to improve the zT of thermoelectric materials, including optimizing carrier concentration, precisely adjusting the band structure to improve the power factor, and using nanotechnology to suppress lattice thermal conductivity. Among the various candidate materials, half-Heusler compounds have become an ideal choice for medium and high temperature thermoelectric applications (700K–1100K) due to their excellent thermal stability, mechanical strength and physical properties. Half-Heusler compounds have a cubic crystal structure similar to MgAgAs and follow the 18-valence electron rule, which enhances the semiconductor stability of the material through strong interactions between bonding and antibonding states. Researchers have further improved the thermoelectric performance of half-Heusler compounds through techniques such as doping, alloying, phase separation and nanostructuring. However, the higher lattice thermal conductivity of traditional half-Heusler compounds (10–20W m -1 K -1 ) limits its thermoelectric efficiency.
[0004] Double half-Heusler compounds have a more complex crystal structure, which significantly reduces the lattice thermal conductivity by introducing disordered scattering and low-frequency phonon modes that reduce group velocity. Compared with traditional ternary half-Heusler compounds, double half-Heusler alloys exhibit lower lattice thermal conductivity due to their complex structure, providing a new direction for the development of high-performance, low-thermal conductivity thermoelectric materials. Summary of the invention
[0005] The purpose of the present invention is to provide a thermoelectric material and a preparation method thereof, specifically to provide a double half-Heusler alloy thermoelectric material with low lattice thermal conductivity and a preparation method thereof, and to prepare a new double half-Heusler alloy with low lattice thermal conductivity by replacing alivalent elements. The double half-Heusler alloy material not only optimizes the thermoelectric performance, further expands and enriches the existing thermoelectric material system, but also provides more options for the fields of thermoelectric power generation and thermoelectric refrigeration.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The first aspect of the present invention provides a thermoelectric material, which is a double half-Heusler alloy thermoelectric material, characterized in that the thermoelectric material is any one of a p-type thermoelectric material or an n-type thermoelectric material, and the chemical formula of the p-type thermoelectric material is Sc 0.6 V 0.5 Co 1-x Ni x Sb, 0≤x≤0.12; the chemical formula of the n-type thermoelectric material is Sc 0.5 V 0.6 Co 1- y Ni y Sb, 0≤y≤0.30.
[0008] Further preferably, the chemical formula of the p-type thermoelectric material is Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb, the chemical formula of the n-type thermoelectric material is Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Sb.
[0009] A second aspect of the present invention provides a method for preparing a thermoelectric material, the method comprising the following steps:
[0010] S1: Sc (scandium), V (vanadium), Co (cobalt), Ni (nickel), and Sb (antimony) are mixed and ground to obtain a mixed powder;
[0011] S2: subjecting the mixed powder in step S1 to spark plasma (SPS) sintering and vacuum packaging treatment in sequence to obtain a thermoelectric material wafer;
[0012] S3: subjecting the thermoelectric material wafer in step S2 to high temperature annealing to obtain a double half-Heusler alloy thermoelectric material with low lattice thermal conductivity.
[0013] Furthermore, in step S1, the Sc, V, Co, Ni, and Sb are Sc blocks, V powder, Co powder, Ni sheets, and Sb particles, respectively.
[0014] Furthermore, in step S1, Sc, V, Co, Ni, and Sb are mixed in a stoichiometric ratio under an argon atmosphere to prevent oxidation during subsequent grinding.
[0015] Furthermore, in step S1, the purity of Sc, V, Co, Ni and Sb is not less than 99.6%.
[0016] Furthermore, in step S1, the purities of Sc, V, Co, Ni, and Sb are 99.6%, 99.9%, 99.9%, 99.7%, and 99.999%, respectively.
[0017] Furthermore, in step S1, the grinding adopts high-energy ball milling, which can fully alloy at room temperature and avoid the safety hazards caused by Sb volatilization and high-temperature treatment; at the same time, this method refines the powder particles, retains more grain boundaries, effectively enhances phonon scattering, and reduces the lattice thermal conductivity of the thermoelectric material.
[0018] Further, in step S1, during the grinding, the grinding speed is 800-1200 r / min, and the grinding time is 20-30 h. Preferably, the grinding speed is 1000 r / min, and the grinding time is 20 h. This ensures that the raw materials are fully crushed and ground, and finally a mixed and uniform powder is obtained.
[0019] Furthermore, in step S1, the particle size of the mixed powder is 0.2-10 μm.
[0020] Furthermore, in step S2, during the sintering, the pressure during the sintering is 40-80 MPa. Preferably, during the sintering, the pressure during the sintering is 50 MPa.
[0021] Furthermore, in step S2, during the sintering, the heating rate is 30-50°C / min, the sintering temperature is 700-1000°C, and the holding time is 5-20min. Preferably, during the sintering, the heating rate is 40°C / min, the sintering temperature is 900°C, and the holding time is 5min.
[0022] Furthermore, in step S2, the diameter of the thermoelectric material disc is 10-15 mm, and the thickness is 0.6-2 mm. Preferably, the diameter of the thermoelectric material disc is 12.7 mm, and the thickness is 1-2 mm.
[0023] Furthermore, in step S2, the vacuum packaging process is to ensure that the thermoelectric material wafer is protected from oxidation and contamination in subsequent operations.
[0024] Further, in step S3, the high temperature annealing is performed at a temperature of 700-900°C for 3-7 days. Preferably, the high temperature annealing is performed at a temperature of 800°C for 5 days. The high temperature annealing treatment of the sample after spark plasma sintering does not eliminate the internal stress caused by rapid sintering, avoids structural defects, promotes grain growth and rearrangement, optimizes the microstructure, and helps to homogenize the material composition, ensure uniform distribution of doping elements, and improve chemical stability.
[0025] Furthermore, in step S3, during the high temperature annealing, the heating rate is 4°C / min.
[0026] Compared with the prior art, the present invention has the following characteristics:
[0027] 1) The present invention provides a double Half-Heusler alloy thermoelectric material with low lattice thermal conductivity. By precisely controlling the Sc / V ratio, p-type and n-type thermoelectric materials were successfully prepared, and both materials showed promising thermoelectric performance;
[0028] 2) The present invention adopts high-energy ball milling to prepare samples, which can fully alloy at room temperature, avoiding the potential safety hazards caused by Sb volatilization and high-temperature treatment; at the same time, this method refines powder particles, retains more grain boundaries, effectively enhances phonon scattering, and reduces the lattice thermal conductivity of thermoelectric materials;
[0029] 3) The present invention performs high temperature annealing on the sample after spark plasma sintering, which does not eliminate the internal stress caused by rapid sintering, avoids structural defects, promotes grain growth and rearrangement, optimizes the microstructure, and helps to homogenize the material composition, ensures uniform distribution of doping elements, and improves chemical stability;
[0030] 4) The present invention uses a double half-Heusler alloy thermoelectric material prepared by substitution of heterovalent elements, accurately controls the Sc / V ratio, successfully obtains p-type and n-type thermoelectric materials based on the same parent compound, and adjusts the carrier concentration by Ni doping. Ni doping not only effectively optimizes the carrier concentration and improves the power factor, but also significantly reduces the lattice thermal conductivity by increasing phonon scattering, enhances the thermoelectric conversion efficiency of the material, and makes the double half-Heusler alloy material have inherent low lattice thermal conductivity. This low thermal conductivity is crucial to improving the zT value of thermoelectric materials and promotes the application prospects of materials in the field of medium and high temperature thermoelectrics;
[0031] 5) The present invention explores more possible chemical components and structures through heterovalent element substitution and develops a series of dual half-Heusler thermoelectric materials with excellent performance—p-type Sc 0.6 V 0.5 Co 1-x Ni xSb and n-type Sc 0.5 V 0.6 Co 1- y Ni y Sb thermoelectric material. Both materials exhibit low lattice thermal conductivity, indicating that they have broad prospects in thermoelectric applications. This innovative method not only expands the material system of Half-Heusler alloys and makes their performance more adjustable, but also provides new ideas for the future development of high-efficiency and low-cost thermoelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 XRD patterns of Sb alloy thermoelectric materials;
[0033] Figure 2 The n-type Sc prepared in Example 2 0.5 V 0.6 Co 0.8 Ni 0.2 Backscattered electron microscope (SEM) image of Sb alloy thermoelectric material and its corresponding EDS spectrum;
[0034] Figure 3 The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Schematic diagram of the relationship between the Seebeck coefficient of Sb alloy thermoelectric materials and temperature;
[0035] Figure 4 The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Schematic diagram of the relationship between the conductivity of Sb alloy thermoelectric materials and temperature;
[0036] Figure 5The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Schematic diagram of the relationship between the thermal conductivity of Sb alloy thermoelectric materials and temperature;
[0037] Figure 6 The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Schematic diagram of the relationship between the lattice thermal conductivity of Sb alloy thermoelectric materials and temperature;
[0038] Figure 7 The p-type Sc prepared in Example 1 and Example 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Schematic diagram of the relationship between the zT value of Sb alloy thermoelectric materials and temperature. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0040] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.
[0041] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0042] Embodiment 1:
[0043] A p-type double half-Heusler thermoelectric material with low lattice thermal conductivity, the chemical formula of which is Sc 0.6 V 0.5 Co 0.92 Ni 0.08Sb, the specific steps of its preparation method are as follows:
[0044] 1) Raw material preparation: In an argon glove box, weigh 99.6% pure Sc block, 99.9% V powder, 99.9% Co powder, 99.7% Ni sheet, and 99.999% Sb pellets according to the stoichiometric ratio, totaling 8 g. After weighing, put all the raw materials into a stainless steel ball mill to obtain a stainless steel ball mill filled with raw materials for standby use.
[0045] 2) High-energy ball milling: The stainless steel ball milling jar containing the raw materials in step 1) is placed in a high-energy ball mill and ball milled at a speed of 1000 r / min for 20 h to ensure that the raw materials are fully crushed and ground, and finally a uniform powder with a particle size of 0.2-10 μm is obtained.
[0046] 3) SPS sintering: Weigh 1-1.5g of the uniform powder in step 2) in an argon glove box and put it into a graphite mold with a diameter of 12.7mm. Place the graphite mold in a spark plasma sintering device and sinter it in a vacuum environment of 50MPa with a heating rate of 40℃ / min and a sintering temperature of 900℃ for 5min. After sintering, cool it naturally to room temperature to obtain a Sc with a diameter of 12.7mm and a thickness of 1-2mm. 0.6 V 0.5 Co 0.92 Ni 0.08 Sb wafer sample.
[0047] 4) Vacuum sealing: The Sc 0.6 V 0.5 Co 0.92 Ni 0.08 The Sb wafer sample is placed in a quartz tube and placed in a tube sealer for vacuum treatment. After the vacuum is completed, the quartz tube is sealed with a tube sealer to ensure that the Sc 0.6 V 0.5 Co 0.92 Ni 0.08 The Sb wafer samples are protected from oxidation and contamination during subsequent operations.
[0048] 5) High temperature annealing: The sealed quartz tube in step 4) is placed in a muffle furnace, heated to 800°C at a heating rate of 4°C / min, and annealed at this temperature for 5 days. After annealing, it is naturally cooled to room temperature in the furnace, and finally a p-type Sc with low lattice thermal conductivity is obtained. 0.6 V 0.5 Co 0.92 Ni 0.08 Sb alloy thermoelectric material.
[0049] Embodiment 2:
[0050] A low lattice thermal conductivity n-type double half-Heusler thermoelectric material, the chemical formula of which is Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Sb, the specific steps of its preparation method are as follows:
[0051] 1) Raw material preparation: In an argon glove box, weigh 99.6% pure Sc block, 99.9% V powder, 99.9% Co powder, 99.7% Ni sheet, and 99.999% Sb pellets according to the stoichiometric ratio, totaling 8 g. After weighing, put all the raw materials into a stainless steel ball mill to obtain a stainless steel ball mill filled with raw materials for standby use.
[0052] 2) High-energy ball milling: The stainless steel ball milling jar containing the raw materials in step 1) is placed in a high-energy ball mill and ball milled at a speed of 1000 r / min for 20 h to fully crush and grind the raw materials to finally obtain a uniform powder with a particle size of 0.2-10 μm.
[0053] 3) SPS sintering: Weigh 1-1.5g of the uniform powder in step 2) in an argon glove box and put it into a graphite mold with a diameter of 12.7mm. Place the graphite mold in a spark plasma sintering device and sinter it in a vacuum environment of 50MPa with a heating rate of 40℃ / min and a sintering temperature of 900℃ for 5min. After sintering, cool it naturally to room temperature to obtain a Sc with a diameter of 12.7mm and a thickness of 1-2mm. 0.5 V 0.6 Co 0.8 Ni 0.2 Sb wafer sample.
[0054] 4) Vacuum sealing: The Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The Sb wafer sample is placed in a quartz tube and placed in a tube sealer for vacuum treatment. After the vacuum is completed, the quartz tube is sealed with a tube sealer to ensure that the Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The Sb wafer samples are protected from oxidation and contamination during subsequent operations.
[0055] 5) High temperature annealing: The sealed quartz tube in step 4) is placed in a muffle furnace, heated to 800°C at a heating rate of 4°C / min, and annealed at this temperature for 5 days. After annealing, it is naturally cooled to room temperature in the furnace, and finally an n-type Sc with low lattice thermal conductivity is obtained. 0.5 V 0.6 Co 0.8 Ni0.2 Sb alloy thermoelectric material.
[0056] The p-type Sc prepared in the above-mentioned Examples 1 and 2 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The results of Sb alloy thermoelectric materials are as follows:
[0057] Figure 1 p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The XRD patterns of Sb alloy thermoelectric materials show that both alloys form single-phase materials with half-Heusler structure. No obvious impurity peaks are observed, indicating that the stoichiometric ratio is well controlled during the synthesis process.
[0058] Figure 2 The n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Backscattered SEM image of Sb alloy and its corresponding EDS spectrum. The SEM image shows the uniform microstructure of the material, and the EDS mapping shows that the alloying elements (Sc, V, Co, Ni, Sb) are evenly distributed in the material, indicating that the elements are well mixed and distributed during the synthesis process, and there is no obvious element segregation or aggregation.
[0059] Figure 3 shows p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The relationship between the Seebeck coefficient of Sb alloy thermoelectric materials and temperature. 0.6 V 0.5 Co 0.92 Ni 0.08 The Seebeck coefficient of Sb is positive, showing p-type semiconductor characteristics, while n-type Sc 0.5 V 0.6 Co 0.8 Ni0.2 The Seebeck coefficient of Sb is negative, showing n-type semiconductor characteristics. As the temperature increases, the p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 The Seebeck coefficient of Sb alloy thermoelectric materials gradually increases and reaches a maximum value at around 700-800K, while the Seebeck coefficient of n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Sb alloy thermoelectric materials show stable negative values in a lower temperature range, which indicates that both materials have good thermoelectric properties in a wide temperature range.
[0060] Figure 4 p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The relationship between the conductivity of Sb alloy thermoelectric materials and temperature. 0.6 V 0.5 Co 0.92 Ni 0.08 The electrical conductivity of Sb alloy thermoelectric materials is higher than that of p-type materials and decreases slightly with increasing temperature, while p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 The electrical conductivity of Sb alloy thermoelectric materials gradually increases with increasing temperature. This change in conductivity is related to the carrier concentration and mobility of the material, indicating that the electrical properties of the two materials are stable and adaptable at different temperatures.
[0061] Figure 5 p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The relationship between the thermal conductivity of Sb alloy thermoelectric materials and temperature. It can be seen that as the temperature increases, the thermal conductivity of both materials gradually decreases, and the n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The thermal conductivity of Sb alloy thermoelectric materials is slightly higher than that of p-type Sc 0.6 V 0.5 Co 0.92Ni 0.08 Sb alloy thermoelectric material. This phenomenon may be related to the lattice thermal conductivity and carrier contribution of the material, indicating that the material has lower thermal conductivity under high temperature conditions, which is conducive to improving the thermoelectric conversion efficiency.
[0062] Figure 6 The relationship between the lattice thermal conductivity of the two materials and temperature is further demonstrated. As the temperature increases, the lattice thermal conductivity gradually decreases, indicating that the material significantly reduces the lattice thermal conductivity by increasing phonon scattering through Ni doping, and effectively suppresses the increase in thermal conductivity through phonon scattering, especially in the high temperature area, the lattice thermal conductivity decreases significantly, reflecting a good phonon thermal conductivity suppression effect.
[0063] Figure 7 p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The relationship between zT and temperature of Sb alloy thermoelectric materials. As the temperature increases, the p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 The zT value of Sb alloy thermoelectric material at 923K reaches 0.41, while n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 The zT value of the Sb alloy thermoelectric material at 973K reaches 0.52, indicating that these two materials show significant improvement in thermoelectric performance in the high temperature region.
[0064] In summary, through the characterization of XRD, SEM and EDS, the p-type Sc 0.6 V 0.5 Co 0.92 Ni 0.08 Sb and n-type Sc 0.5 V 0.6 Co 0.8 Ni 0.2 Sb alloy thermoelectric materials have excellent structural stability and uniformity. Especially in the high temperature range, the zT values of these two materials are significantly improved, indicating that they have broad application prospects in the field of medium and high temperature thermoelectric applications.
[0065] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A thermoelectric material, which is a double half-Heusler alloy thermoelectric material, characterized in that: The thermoelectric material is any one of a p-type thermoelectric material and an n-type thermoelectric material. The chemical formula of the p-type thermoelectric material is Sc 0.6 V 0.5 Co 1- x Ni x Sb, 0≤x≤0.12; the chemical formula of the n-type thermoelectric material is Sc 0.5 V 0.6 Co 1-y Ni y Sb, 0≤y≤0.
30.
2. A method for preparing a thermoelectric material according to claim 1, characterized in that: The method comprises the following steps: S1: Sc, V, Co, Ni and Sb are mixed and ground to obtain a mixed powder; S2: sintering and vacuum packaging the mixed powder in step S1 in sequence to obtain a thermoelectric material wafer; S3: subjecting the thermoelectric material wafer in step S2 to high temperature annealing to obtain a double half-Heusler alloy thermoelectric material.
3. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S1, Sc, V, Co, Ni, and Sb are mixed in a stoichiometric ratio under an argon atmosphere.
4. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S1, the purity of Sc, V, Co, Ni and Sb is not less than 99.6%.
5. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S1, during the grinding, the grinding speed is 800-1200 r / min and the grinding time is 20-30 h.
6. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S1, the particle size of the mixed powder is 0.2-10 μm.
7. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S2, during the sintering, the pressure during sintering is 40-80 MPa.
8. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S2, during the sintering, the heating rate is 30-50°C / min, the sintering temperature is 700-1000°C, and the holding time is 5-20min.
9. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S2, the thermoelectric material disc has a diameter of 10-15 mm and a thickness of 0.6-2 mm.
10. The method for preparing a thermoelectric material according to claim 2, characterized in that: In step S3, the high temperature annealing is performed at a temperature of 700-900° C. for 3-7 days.